Pelatihan Budidaya Tanaman Sayuran Menggunakan Metode Hidroponik Dengan Memanfaatkan Botol Bekas Sebagai Media Tanam - Ningsih, Winnarti; Billah, Mu'tasim; Laily, Dona Waahyuning (Universitas Gajah Putih, Indonesia, 2023)
Vegetables play an important role for humans, because they contain little fat and carbohydrates, but contain lots of vitamins, nutrients that are very important for health. Hydroponics is a method of cultivating plants that only requires water as a growing medium without using soil. The use of this hydroponic concept is a simple method that can be used to increase people's attention to the environment by using used bottles. Based on the things that have been described, the author raises the topic of community service entitled